Reducing Crosstalk Induced Delay and Peak Noise in Carbon Nanotube Interconnects - Sathyakam, Piratla U.; Mallick, Partha S. (Current Nanoscience, 2018)
Background: Crosstalk will be a major concern in future nano ICs where the components will be scaled down to a few nanometers. In particular, modeling of CNT based interconnects shows that they will suffer from crosstalk when fabricated at smaller technology nodes. Objective: This paper presents reduction of crosstalk and noise in CNT bundle interconnects. We propose the use of small diameter semiconducting CNTs (s-CNTs) as electromagnetic interference (EMI) shields for CNT bundle interconnects. Methods: The coupling capacitance of the proposed CNT bundle structure shows that crosstalk can be reduced significantly by using small diameter s-CNTs. We perform SPICE analysis to show the reduction in crosstalk and peak noise. Results: The proposed bundle geometry reduces 46% crosstalk induced delay and 23% output peak noise as compared to conventional CNT interconnects. Conclusions: Small diameter semiconducting CNTs can be used as EMI shields to reduce crosstalk and noise in CNT interconnects.
Keywords: peak noise